Concerning Concealed Weapons, in Alameda Encinal, May 3, 1882, at 3 - (:unkn) unknown (My University, 1882)
Prohibited concealed carrying of any pistol, slung-shot, brass or iron knuckles, iron bars "such as are usually carried by Chinamen," sand clubs, dirk, Bowie-knife, dangerous weapons, deadly weapons. Violators punished by fine not exceeding one hundred dollars, or imprisonment not exceeding fifty days, or both.
Keywords: CARRY - CONCEALED